Viral Takeover of the Host Ubiquitin System - Gustin, Jean K.; Moses, Ashlee V.; Früh, Klaus; Douglas, Janet L. (Frontiers in Microbiology, 2011)
Like the other more well-characterized post-translational modifications (phosphorylation, methylation, acetylation, acylation, etc.), the attachment of the 76 amino acid ubiquitin (Ub) protein to substrates has been shown to govern countless cellular processes. As obligate intracellular parasites, viruses have evolved the capability to commandeer many host processes in order to maximize their own survival, whether it be to increase viral production or to ensure the long-term survival of latently infected host cells. The first evidence that viruses could usurp the Ub system came from the DNA tumor viruses and Adenoviruses, each of which use Ub to dysregulate the host cell cycle. Today, the list of viruses that utilize Ub includes members from almost every viral class, including both RNA and DNA viruses. Among these, there are examples of Ub usage at every stage of the viral life cycle, and these entail both ubiquitination and de-ubiquitination. In addition to viruses that merely modify the host Ub system, many of the large DNA viruses encode their own Ub modifying machinery. In this review, we highlight the latest discoveries regarding the myriad ways that viruses utilize Ub to their advantage.